FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN DALAM MENGGUNAKAN KREDIT SAHABAT DI BUMDES BATU PENANING DESA BERARE KECAMATAN MOYO HILIR - Wiwin Mindartini; Lukman Hakim; Alia Wartiningsih; Muhammad Aries Zukhri Angkasa; Syahdi Mastar (Alia Wartiningsih, M.Si, 2026)
This study aimed to analyze the factors influencing consumer behavior in the use of Kredit Sahabat and to examine the impact of its utilization on community welfare. The research was conducted in May 2025 in Berare Village. Data were collected through observation, interviews, and documentation. A total of 30 respondents were selected using proportional sampling. Consumer behavior was analyzed using both qualitative and quantitative approaches. The qualitative analysis employed the Likert Summated Rating (LSR) scale to assess the influence of cultural, social, personal, and psychological factors on consumer behavior. Meanwhile, the quantitative analysis included the Normality Test, Correlation Test, Simultaneous Test (F-test), and Partial Test (t-test). The results revealed that among the four factors examined, only the psychological factor significantly influenced consumer behavior in using Kredit Sahabat, as indicated by a significance value of 0.003 (< 0.05) and a t-value of 3.271, which exceeded the t-table value of 2.042. Therefore, the null hypothesis (H?) was rejected, and the alternative hypothesis (H?) was accepted. Furthermore, the findings indicate that the use of Kredit Sahabat has a positive impact on improving community welfare.